The 4th EWaS International Conference: Valuing the Water, Carbon, Ecological Footprints of Human Activities 2020
DOI: 10.3390/environsciproc2020002034
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Modeling on Fate and Transport of Pollutants in the Vadose Zone

Abstract: Soil contamination is an issue of paramount importance to assess human health (HHRA) as well as ecological (ERA) risk assessment. To analyze risk scenarios related to contaminated soils, the identification of sources, either of primary or secondary type, as well as the assessment of propagation and fate processes is needed. Although many studies refer to the transport of pollutants in fully saturated porous media, little efforts have been made concerning the case of partially saturated soils so far. The matter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…As a sink of various organic contaminants, soil could affect the fate of organic pollutants (e.g., organohalides) and their subsequent transport to other environmental matrices, including groundwater and atmosphere. , The fate of organic pollutants in soil was synergistically determined by combined biophysiochemical processes, including accumulation and transformation through sorption/desorption, abiotic degradation, and biotransformation, which highly depended on the soil compositions and physiochemical properties as well as soil microbiomes. , In China, according to the National Soil Contamination Survey Bulletin published in 2014, around 16% of surveyed soil samples had at least one organic pollutant exceeding standard values, particularly the organohalide pollutants . Similarly, an agricultural soil survey reported that volatile organohalides were present in all tested samples.…”
Section: Introductionmentioning
confidence: 99%
“…As a sink of various organic contaminants, soil could affect the fate of organic pollutants (e.g., organohalides) and their subsequent transport to other environmental matrices, including groundwater and atmosphere. , The fate of organic pollutants in soil was synergistically determined by combined biophysiochemical processes, including accumulation and transformation through sorption/desorption, abiotic degradation, and biotransformation, which highly depended on the soil compositions and physiochemical properties as well as soil microbiomes. , In China, according to the National Soil Contamination Survey Bulletin published in 2014, around 16% of surveyed soil samples had at least one organic pollutant exceeding standard values, particularly the organohalide pollutants . Similarly, an agricultural soil survey reported that volatile organohalides were present in all tested samples.…”
Section: Introductionmentioning
confidence: 99%
“…The available numerical methods to investigate the behavior of particles make it possible for machine constructors to track the forces acting on a transported material. The most important ones are normal forces and tangential forces resulting from the collision of particles with the walls of transport equipment [7][8][9]. They affect mainly the quality of the transported material.…”
Section: Introductionmentioning
confidence: 99%